The “Cordial Partnership”. Building deeper German-Russian cooperation during the SPD-Bündnis 90/Die Grünen coalition government of 1998–2005 - Koszel, Bogdan (Roczniki Nauk Społecznych, 2024)
The author analyzes the principles and reasons for Germany’s involvement in the years 1998–2005 in the field of economic cooperation, cooperation in building European and world security and attracting the Russian Federation to the European Union. Germany’s support for the banner of the ruling SPD-Green coalition, which has the rule of law and human rights due to favorable economic conditions and the warming of Russi’s international image, was in contradiction with Vladimir Putin’s authoritarian rule and gagging of the opposition.